ANALISIS STATIONERITAS BETA DI BURSA EFEK JAKARTA - M. Fakhri Husein (KINERJA, 2004)
This research tries to explore the issue of beta stationarity on Jakarta Stock Exchange. The tests indicate that the stationarity beta is dependent on the estimation interval. Investor will be better off using a longer estimation period. Understanding beta make it easier for investors to predict their future investments. By using 92 samples listed in BEJ, correlation analysis convey that beta tends not to stay in the same risk class from one period to the next.Keywords: Stasionarity, Beta, correlation coefficient